DESAIN REAR SPRING BRACKET DENGAN MENGGUNAKAN SOFTWARE SOLIDWORK DI PT. GEMALA KEMPA DAYA - , HERU SETYAWAN ABRIYANTO, Ir. Bambang Suharnadi, M.T. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Rear spring bracket 48414-0W020 is one of component of frame chassis Hino 479w type 51000-0W903. In a current time, that component is not manufactured by PT. Gemala Kempa Daya. That component is manufactured by other companies but assembled along with another frame chassis components Hino 479w type 51000-0W903 which are manufactured by PT. Gemala Kempa Daya. Moving on from that issue, the author trying to make a new design of rear spring bracket that can be produced by PT. Gemala Kempa Daya and can replace the current design of rear spring bracket 48414-0W020. To make the design of new rear spring bracket, the author using software SolidWork Premium 2012 to create design drawings as well as to simulate static analysis that occurs on the design. The new design of rear spring bracket that made by the author is consists 6 parts, they are Head, Body, Holder 01, Holder 02, Penguat 01, and Penguat 02. Based on static analysis which performed by Solidwork Simulation for 18375 N loading, the maximum stress which affected on the design is 91,972 N/mm2, the safety factor of the design is 3,2, and the maximum deflection that occurs on the design is 0,165 mm.